Choroidal neovascularization silent on optical coherence tomography: report of two cases - Borges,Felipe Placeres (2017)
ABSTRACT Herein, we report two cases of vision loss after successful cataract surgery, associated with drusenoid retinal pigment epithelial detachment without features of choroidal neovascularization on optical coherence tomography along with angiographic examinations suggestive of choroidal neovascularization in which anatomical and functional improvements were achieved with intravitreal injections of anti-vascular endothelial growth factor.